The Role of T-Regulatory Cells in the Immune System and Their Therapeutic Potential in Inflammation and Lung Cancer - Ivanovich, Kobylyansky Viacheslav (Trends in Immunotherapy, 2025)
One of the key links of the immune system, which plays a crucial role in maintaining homeostasis and lung function, is T-regulatory cells (Treg). Their suppressive effect on the immune system predetermines the potential of various modulating effects, taking into account the pathogenetic features of the pathology, which underlie innovative methods of therapy, including in pulmonology. However, awareness of them remains insufficient and, in some cases, contradictory, which requires appropriate consideration and analysis, which became the purpose of this work. An analysis of 69 literary sources selected from different databases of biomedical scientific information was carried out. The analysis showed that targeted methods for the treatment of inflammation and tumors are developed based on the generally accepted paradigm about Treg and are aimed at their modulation. In inflammation, activation of Treg, exerting a suppressive effect on T-effector cells, reduces it. In tumors, their depletion, promoting the expression of T-effector cells, including antitumor cells, slows their growth. This is achieved by various direct or indirect methods of influence. Along with this, some researchers suggest using a depleting effect on Tregs in inflammation, and similarly, in both tumor and inflammatory processes, which contradicts the generally accepted paradigm regarding Tregs. Thus, a modulating effect on Tregs can have a therapeutic effect on both inflammation and tumors, with a differentiated consideration of the mechanisms of their development. Methods of treating inflammation that contradict the generally accepted paradigm regarding Tregs remain unsupported by a sufficient evidence base and are untenable.